Rabbinic Notes to Graeco-Coptica - Shperber, Daniʾel (AJS review, 1979)
In Le muséon 82 (1969): 85-86, and 89 (1976): 311-12 James Drescher, in a series entitled “Graeco-Coptica,” discussed the word (and , showing that in late Greek and in Coptic it bears the additional meaning of “alms, charity.” To his discussion should be added the remarks of Saul Lieberman, in an article entitled “, Charity, Alms,” Journal of Biblical Literature 65 (1946): 69-72. There Lieberman brings considerable evidence for in this special usage in early Christian literature. He also shows there that a similar semantic development took place in the case of the Hebrew word (and its Aramaic equivalents), which came likewise to mean “alms, charity.” (See further his note apud Leviticus Rabba, ed. Mordecai Margulies [Jerusalem, 1958], pt. 4, p. 870 to line 56.)